24 avril : journée de solidarité avec les étudiants et la jeunesse en lutte contre le colonialisme, pour l'independence nationale et la coexistence pacifique
Large red number '24' over black background; all text Poster advertising day of solidarity with the International Union of Students' causes, 24 April PO-1488